Perancangan Sistem Pelayanan Publik Desa (Studi Kasus: Desa Serambi Gunung, Kabupaten Seluma) - Geri Melano Evandra; Pahrizal Pahrizal; Yuza Reswan; Muntahanah Muntahanah (Jurnal Media Infotama, 2025)
This study aims to design a web-based public service system for Serambi Gunung Village, Seluma Regency, improve the effectiveness and efficiency of village administrative services. The background of this research stems from the continued use of manual processes in village public services, which result in delays, risks of document loss, and low service transparency. Chosen due to its iterative and participatory approach, involving users directly in the design process, thus allowing the system to be developed according to actual field needs. The research was conducted from April to July 2025 using a qualitative method with data collection techniques including observation, interviews, literature review, and documentation. The results show that the system developed successfully integrates administrative services such as ID card (KTP) processing, family card (KK) issuance, correspondence, social assistance, and citizen complaints into a single digital platform that is easily accessible to the public. The system design includes UML diagrams (use case, activity, class diagrams), user interfaces for both administrators and citizens, as well as database structures and a search algorithm for service requests. System testing was carried out using the blackbox method to ensure that all functions work as required. The study concludes that the web-based village public service system designed using the prototype method can enhance service quality, speed up administrative processes, and promote transparency and public participation in village governance